2000
DOI: 10.1001/archsurg.135.12.1428
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Anatomy of the Spinal Accessory Nerve and the Trapezius Branches of the Cervical Plexus

Abstract: Background: A thorough understanding of the topographical anatomy of the spinal accessory nerve and the cervical plexus branches is a basic prerequisite for positive results when operating on the neck. Objective: To give an exact description of the topographical and surgical anatomy of the spinal accessory nerve (SAN) and the trapezius branches of the cervical plexus. Design: Anatomic analysis of the SAN and the trapezius branches of the cervical plexus. Setting: The topographical anatomy of the SAN and the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 21 publications
7
95
0
3
Order By: Relevance
“…In a recent study, this communication was found in 22 neck dissections (11 cadavers) and most of them were observed at the inferior border of submandibular gland (Domet et al, 2005). Communications between the cervical plexus and spinal accessory nerve are also well known and have been reported in the past (Soo et al, 1986;Kierner et al, 2000). Branches of cervical plexus rarely communicate with phrenic nerve (Loukas et al, 2006).…”
Section: Discussionmentioning
confidence: 88%
“…In a recent study, this communication was found in 22 neck dissections (11 cadavers) and most of them were observed at the inferior border of submandibular gland (Domet et al, 2005). Communications between the cervical plexus and spinal accessory nerve are also well known and have been reported in the past (Soo et al, 1986;Kierner et al, 2000). Branches of cervical plexus rarely communicate with phrenic nerve (Loukas et al, 2006).…”
Section: Discussionmentioning
confidence: 88%
“…Communications between TCCN and the GAN as well as some cranial nerves usually exist and are reported in the past [1,3,4]. Biglioli et al [5] have been reported an anastomosis between the TCCN and anterior branch of GAN.…”
Section: Discussionmentioning
confidence: 99%
“…There are several nerves arising from this point, including the great auricular, lesser occipital, transverse cervical, and supraclavicular nerves (Anderson et al, 2008;Aramrattana et al, 2005;Dailiana et al, 2001). From the punctum nervosum, the accessory nerve courses inferolaterally, then ramifies into numerous branches supplying the trapezius (Aramrattana et al, 2005;Clemente, 1985;Dailiana et al, 2001;Kierner et al, 2000;Roman 1981;Shiozaki et al, 2000) (Fig.9). In addition to the accessory nerve, motor branches of the cervical plexus derived from the C2-C3 anterior rami participate in innervation of the sternocleidomastoid and trapezius muscles (Aramrattana et al, 2005;Bertrand, 2004;Clemente, 1985;Dailiana et al, 2001;Pu et al, 2008;Roman 1981;Stacey et al, 1995;Zhao et al, 2006).…”
Section: Surgical Anatomy Of the Accessory Nerve And Its Peripheral Bmentioning
confidence: 99%
“…The nerves which contribute to the innervation of cervical dystonic muscles are summarized in Table 3 ( Anderson et al, 2008;Aramrattana et al, 2005;Bertrand, 2004;Clemente, 1985;Dailiana et al, 2001;Frank et al, 1997;Kierner et al, 2000;Pu et al, 2008;Roman, 1981;Stacey et al, 1995;Taira, 2009;Zhao et al, 2006 Table 3. The muscles in the neck region associated with cervical dystonia and their nerve supply…”
Section: Conclusion Of the Nerve Supplymentioning
confidence: 99%